Elsa DORLIN - Se défendre - Une philosophie de la violence - UPOP Marseille (2020)
Se défendre. Une philosophie de la violence Conférence d’Elsa DORLIN En 1685, le Code noir défendait « aux esclaves de porter aucune arme offensive ni de gros bâtons » sous peine de fouet. Au XIXe siècle, en Algérie, l’État colonial interdisait les armes aux indigènes, tout en accordant aux colons le droit de s’armer. Aujourd’hui, certaines vies comptent si peu que l’on peut tirer dans le dos d’un adolescent noir au prétexte qu’il était « menaçant ». Une ligne de partage oppose historiquement les corps « dignes d’être défendus » à ceux qui, désarmés ou rendus indéfendables, sont laissés sans défense. Ce « désarmement » organisé des subalternes pose directement, pour tout élan de libération, la question du recours à la violence pour sa propre défense. Des résistances esclaves au ju-jitsu des suffragistes, de l’insurrection du ghetto de Varsovie aux Black Panthers ou aux patrouilles queer, Elsa Dorlin retrace une généalogie de l’autodéfense politique. Sous l’histoire officielle de la légitime défense affleurent des « éthiques martiales de soi », pratiques ensevelies où le fait de se défendre en attaquant apparaît comme la condition de possibilité de sa survie comme de son devenir politique. Cette histoire de la violence éclaire la définition même de la subjectivité moderne, telle qu’elle est pensée dans et par les politiques de sécurité contemporaines, et implique une relecture critique de la philosophie politique, où Hobbes et Locke côtoient Frantz Fanon, Michel Foucault, Malcolm X, June Jordan ou Judith Butler.
Keywords: antiracisme; approches et analyses; cours; discipline; militance; patriarcat; philosophie; pol5480; premier cycle; racisme; ressource en ligne; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Les lieux de la culture: une théorie postcoloniale - Bhabha, Homi K.; Bouillot, Françoise (Petite biblio Payot, 2019)
Sommaire"Salué aussi bien par Edward Said que par Toni Morrison ou J.M. Coetzee, Homi K. Bhabha est l un des théoriciens les plus importants et les plus influents du postcolonialisme. S'appuyant sur la littérature, la philosophie, la psychanalyse et l'histoire, il invite notamment à repenser les questions très actuelles d'identité et d'appartenance nationales ; à dépasser, grâce au concept très fécond d'hybridité culturelle, la vision d'un monde dominé par l'opposition entre soi et l'autre ; à saisir comment, par le biais de l'imitation et de l'ambivalence, les colonisés introduisent chez leurs colonisateurs un sentiment d'angoisse qui les affaiblit considérablement ; ou encore, plus largement, à comprendre les liens qui existent entre colonialisme et globalisation." -- Résumé de l'éditeur.
Keywords: approches et analyses; arts; com5170; cours; discipline; har4600; histoire; histoire et politique; identités; philosophie; postcolonialisme; premier cycle; psychanalyse; sciences; sciences humaines; système colonial; systèmes d'oppressions; thématiques; études littéraires

La colonialité du genre - Lugones, María (Les cahiers du CEDREF, 2019)
Keywords: approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; philosophie; pol4212; premier cycle; ressource en ligne; science politique; science politique et droit; sciences humaines; système colonial; systèmes d'oppressions; thématiques

The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Polyrhythmic dance currents: Race multiculturalism and the montreal dance community - Templeton, Melissa (Université de Californie à Riverside, 2012)
This dissertation examines African and African Diaspora concert dance in Montreal in relation to Canadian multicultural policies and Québec nationalism. The multiple layers of colonization and various waves of immigration to Québec have made the province a unique nation with its own complex history of racial construction, quite unlike the racial histories of the U.S. or the rest of Canada (though still greatly informed by these racial paradigms). In the debates that arise in Québec over multiculturalism, language is often seen as the main cultural component in need of preservation. However, this focus on language often masks other elements at play in these cultural debates, in particular, how "race" informs notions of cultural belonging in Québec. A focus on African Diaspora dance in Montreal (Québec's largest and most demographically varied city) helps bring racial construction to the fore for two reasons. First, language differences do not distinguish Québec's Black community from the white French-Canadian majority as Québec's Black population is comprised mainly of French-speakers, and accordingly, studying Montreal's African Diaspora reduces the significance of linguistic difference. Second, concentrating on dance practices helps identify how the Montreal public interprets bodies and their cultural meanings. By analyzing the public support and critical reception of African Diaspora dance practices in Montreal, this dissertation examines how racial difference is constructed through multicultural rhetoric, policies, and debates about dance; it also suggests that dance practitioners have the ability to change and inform these constructed identities and the social landscape that frames them. To conduct this research, I use archival material along with personal interviews and participant-observer ethnography to examine: the early visits of Les Ballets Africains to North America (with a particular focus on Montreal); the Montreal-based company Les Ballets Jazz; the 1999 Montreal festival Afrique: Aller/Retour; and the work of Contemporary African dance choreographer Zab Maboungou. With these subjects, my projects contributes a partial history of African Diaspora dance in Montreal and analyzes the effectiveness and the shortcomings of Canadian Multiculturalism on this community.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; danse; diaspora africaine; discipline; montréal; multiculturalisme; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Towards a decolonial feminism - Lugones, Maria (Hypatia, 2010)
Dans « Heterosexualism and the Colonial/Modern Gender System » (Lugones 2007), j’ai proposé de lire la relation entre le colonisateur et le colonisé en termes de genre, de race et de sexualité. Je n’entendais pas par là ajouter une lecture genrée et une lecture raciale aux relations coloniales déjà comprises. J’ai plutôt proposé une relecture de la modernité coloniale capitaliste moderne elle-même. C’est parce que l’imposition coloniale du genre traverse les questions d’écologie, d’économie, de gouvernement, de relations avec le monde des esprits et de connaissance, ainsi que les pratiques quotidiennes qui nous habituent à prendre soin du monde ou à le détruire. Je propose ce cadre non pas comme une abstraction de l’expérience vécue, mais comme une lentille qui nous permet de voir ce qui est caché de notre compréhension de la race et du genre et de la relation de chacun avec l’hétérosexualité normative.
Keywords: amériques; approches et analyses; colonialité du genre; corps; discipline; féminisme décolonial; histoire et politique; hétérosexisme; philosophie; philosophie politique; racisme; régions géographiques; sciences humaines; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Contract and domination - Pateman, Carole; Mills, Charles W. (Polity, 2007)
« Contract and Domination offers a bold challenge to contemporary contract theory, arguing that it should either be fundamentally rethought or abandoned altogether. Since the publication of John Rawls's A Theory of Justice, contract theory has once again become central to the Western political tradition. But gender justice is neglected and racial justice almost completely ignored. Carole Pateman's and Charles Mills's earlier books, The Sexual Contract (1988) and The Racial Contract (1997), offered devastating critiques of gender and racial domination and the contemporary contract tradition's silence on them. Both books have become classics of revisionist radical democratic political theory. Now Pateman and Mills are collaborating for the first time in an interdisciplinary volume, drawing on their insights from political science and philosophy. They are building on but going beyond their earlier work to bring the sexual and racial contracts together. In Contract and Domination, Pateman and Mills discuss their differences about contract theory and whether it has a useful future; excavate the (white) settler contract that created new civil societies in North America and Australia; argue via a "non-ideal" contract for reparations to black Americans; confront the evasions of contemporary contract theorists; explore the intersections of gender and race and the global sexual-racial contract; and reply to their critics. »--Page 4 de la couverture.
Keywords: approches et analyses; capitalisme; com5170; contrat social; cours; discipline; histoire et politique; intersectionnalité; patriarcat; philosophie; philosophie politique; pol4212; premier cycle; racisme; rapports de domination; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques